Comparison of Fabrication Technique and Carrier Oil to Curcumin Nanoemulsion Properties - Zubaidah Ningsih; Sepriana Puspita Dewi Syaiful; Maria L.A.D Lestari; Diah Mardiana; Budi Kamulyan (Chemistry Department, The University of Brawijaya, 2023)
Turmeric (Curcuma longa L.) is included in the rhizome plant containing curcumin which has various therapeutic properties. However, curcumin has poor bioavailability. The manufacture of nanoemulsion is expected to increase curcumin bioavailability. This study aims to compare 3 methods (wet-ball milling, ultrasonication and microfluidic) and 3 carrier oils (soybean, virgin coconut, and olive oil) in the production of curcumin nanoemulsion. Wet-ball milling reduces particle size through grinding process using milling beads in liquid medium. Microfluidic decreases the particle size via collision of emulsion components in microchannel while ultrasound utilizes sound-wave energy to break down the particle size. Parameters compared were particle size, polydispersity index and entrapment efficiency. Particle size and polydispersity index were observed using Particle Size Analyzer with Dynamic Light Scattering technique while entrapment efficiency was measured based on the curcumin absorbance in UV-Visible spectrophotometer at 420 nm. Our study concludes that microfluidic is the most effective and efficient fabrication method which produces the smallest particle size and polydispersity index compared to ultrasonication and microfluidic. The resulting particle sizes using microfluidic are 154, 140 and 132 nm with polydispersity index of 0.224; 0.200and 0.208 insoybean,virgin coconut, and oliveoil respectively. However, entrapment efficiency is best achieved using wet-ball milling method with the average value of 49±10%. Soybean oil appears to be the most curcumin solubilizing oil compared to olive and virgin coconut oil. Thus, it can be concluded that fabrication methods and carrier oils determine curcumin nanoemulsion properties.